2022
DOI: 10.3389/fnins.2022.943355
|View full text |Cite
|
Sign up to set email alerts
|

Influence of denaturants on amyloid β42 aggregation kinetics

Abstract: Amyloid formation is linked to devastating neurodegenerative diseases, motivating detailed studies of the mechanisms of amyloid formation. For Aβ, the peptide associated with Alzheimer’s disease, the mechanism and rate of aggregation have been established for a range of variants and conditions in vitro and in bodily fluids. A key outstanding question is how the relative stabilities of monomers, fibrils and intermediates affect each step in the fibril formation process. By monitoring the kinetics of aggregation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Although the spatial resolution of the liquid-based AFM is limited to relatively large changes in single protein shape or dissociation into subunits, the benefits of this approach could start to address an important unmet need to investigate conformational changes and hydrophobic hydration effects that can occur during the denaturation. For example, it has been recently shown that urea can modulate growth and aggregation kinetics of amyloid beta peptides implicated in the pathology of Alzheimer’s disease, , which we anticipate can now be visualized, and morphological changes quantified one protein at a time.…”
Section: Discussionmentioning
confidence: 97%
“…Although the spatial resolution of the liquid-based AFM is limited to relatively large changes in single protein shape or dissociation into subunits, the benefits of this approach could start to address an important unmet need to investigate conformational changes and hydrophobic hydration effects that can occur during the denaturation. For example, it has been recently shown that urea can modulate growth and aggregation kinetics of amyloid beta peptides implicated in the pathology of Alzheimer’s disease, , which we anticipate can now be visualized, and morphological changes quantified one protein at a time.…”
Section: Discussionmentioning
confidence: 97%
“…A comprehensive analysis of the impact that urea and guanidinium have on the aggregation process of the peptide Aβ42, a natively unfolded peptide whose aggregation is believed to be heavily implicated in the insurgence and progression of Alzheimer's disease, has been reported by Linse, Knowles, and colleagues [125]. These authors demonstrated that urea, as a non-ionic denaturant, reduces the overall aggregation rate with a stronger effect on nucleation compared to the elongation steps.…”
Section: Effects Of Chemical Denaturants On Amyloid-like Aggregatesmentioning
confidence: 92%
“…Chemical denaturants may operate at different stages of the amyloid formation process and may either favor or disfavor it [125]. In some cases, it has been observed a reduction of the lag phase.…”
Section: Effects Of Chemical Denaturants On Amyloid-like Aggregatesmentioning
confidence: 99%
“…Consequently, denaturants are more likely to inhibit than accelerate fibril formation from disordered proteins. Aβ42 fibrillation is inhibited by urea [ 134 , 135 ] and guanidinium chloride at concentrations above 1 M [ 135 , 136 ] due to a decrease in the rate of both primary and secondary nucleation. Interestingly, at low concentrations, guanidinium chloride act as an osmolyte, increasing the rate of beta-amyloid fibrillation, likely due to the electrostatic interactions with the ions formed upon its dissociation.…”
Section: Effect Of Inhibitor Binding On Amyloid Fibril Formationmentioning
confidence: 99%